Eastern Tropical Indian Ocean individual foraminiferal analyses (IFA) of Globigerinoides ruber isotopes from the Late Holocene and LGM - Kaustubh Thirumalai; Pedro N DiNezio; Jessica E Tierney; Martin Puy; Mahyar Mohtadi (PANGAEA, 2019)
This dataset presents measurements of individual foraminiferal analyses (IFA) of stable oxygen and carbon isotopes in tests of planktic foraminifera Globigerinoides ruber, obtained from a series of four eastern tropical Indian Ocean sediment cores. The IFA dataset focuses on two time periods: the Late Holocene (0-2 ka) and the Last Glacial Maximum (19-21 ka).
Supplement to: Thirumalai, K et al. (2019): An El Niño mode in the glacialIndian Ocean? Paleoceanography and Paleoclimatology, 34(8), 1316-1327, https://doi.org/10.1029/2019PA003669